Rare protein-altering variants in ANGPTL7 lower intraocular pressure and protect against glaucoma - Tanigawa Yosuke; Wainberg Michael; Karjalainen Juha; Kiiskinen Tuomo; Venkataraman Guhan; Lemmelä Susanna; Turunen Joni A; Graham Robert R; Havulinna Aki S; Perola Markus; Palotie Aarno; Daly Mark J; et al. (PUBLIC LIBRARY SCIENCE, 2022)
Protein-altering variants that are protective against human disease provide in vivo validation of therapeutic targets. Here we use genotyping data from UK Biobank (n = 337,151 unrelated White British individuals) and FinnGen (n = 176,899) to conduct a search for protein-altering variants conferring lower intraocular pressure (IOP) and protection against glaucoma. Through rare protein-altering variant association analysis, we find a missense variant in ANGPTL7 in UK Biobank (rs28991009, p.Gln175His, MAF = 0.8%, genotyped in 82,253 individuals with measured IOP and an independent set of 4,238 glaucoma patients and 250,660 controls) that significantly lowers IOP (beta = -0.53 and -0.67 mmHg for heterozygotes, -3.40 and -2.37 mmHg for homozygotes, P = 5.96 x 10-9 and 1.07 x 10-13 for corneal compensated and Goldman-correlated IOP, respectively) and is associated with 34% reduced risk of glaucoma (P = 0.0062). In FinnGen, we identify an ANGPTL7 missense variant at a greater than 50-fold increased frequency in Finland compared with other populations (rs147660927, p.Arg220Cys, MAF Finland = 4.3%), which was genotyped in 6,537 glaucoma patients and 170,362 controls and is associated with a 29% lower glaucoma risk (P = 1.9 x 10-12 for all glaucoma types and also protection against its subtypes including exfoliation, primary open-angle, and primary angle-closure). We further find three rarer variants in UK Biobank, including a protein-truncating variant, which confer a strong composite lowering of IOP (P = 0.0012 and 0.24 for Goldman-correlated and corneal compensated IOP, respectively), suggesting the protective mechanism likely resides in the loss of interaction or function. Our results support inhibition or down-regulation of ANGPTL7 as a therapeutic strategy for glaucoma.
Author summary
Glaucoma is a common eye disease that damages the optic nerve. Using intraocular pressure, which is a known modifiable risk factor and predictive measure for glaucoma, genome-wide association studies have identified dozens of genetic variants likely affecting disease risk. However, the identification of potential therapeutic targets from those discoveries has been challenging because the functional consequences and the causal variants of the suggested common variant associations are typically unclear. Here, we present a strategy to scan for rare protein-altering variants, which provides direct insights into the functional consequence and the therapeutic effects, using more than 514,000 individuals with European ancestries in two population cohorts in the UK and Finland. We discover an allelic series of multiple rare ANGPTL7 missense and nonsense variants in UK Biobank that lower intraocular pressure and reduces the risk of glaucoma. We further identify an ANGPTL7 missense variant in FinnGen cohort with more than 50-fold enrichment in the Finnish population that provides protection against glaucoma and its subtypes. Our results highlight the benefits of multi-cohort analysis for the discovery of rare protein-altering variants in common diseases and indicate ANGPTL7 as a therapeutic target for glaucoma.